The red millionaire : a political biography of Willi Münzenberg, Moscow's secret propaganda tsar in the West - McMeekin, Sean, 1974- (Yale University Press, 2003)
A committed communist and a tireless con man, Lenin's friend and the Soviet Union's most persuasive myth-maker, Willy Munzenberg changed the course of European history. Willy Munzenberg - an Old Bolshevik who was also a self-promoting tycoon - became one of the most influential communist operatives in Europe between the World Wars. He created a variety of front groups that recruited well-known political and cultural figures to work on behalf of the Soviet Union and its causes, and he ran an international media empire that churned out enormous amounts of propaganda and raised money for Communist concerns. Sean McMeekin tells Munzenberg's story, arguing that his financial chicanery and cynical propaganda efforts weakened the non-communist left, enraged the right and helped feed a cycle that culminated in Nazism. Drawing extensively on recently opened Moscow archives, McMeekin describes how Munzenberg parlayed his friendship with Lenin into a personal fortune and how Munzenberg's mysterious financial manipulations outraged social democrats and lent rhetorical ammunition to the Nazis. His book sheds light on comintern finances, propaganda strategy, the use of front organizations to infiltrate non-communist circles and the breakdown of democracy in the Weimar republic.